The Effect of Moringa Leaf Powder (Moringa Oleifera) on Breast Milk Production in Post Partum Mothers: Pengaruh Bubuk Daun Kelor (Moringa Oleifera) Terhadap Produksi Asi pada Ibu Nifas - Dinengsih, Sri; Agnestiani, Maesaroh; Kundaryanti, Rini (Universitas Muhammadiyah Sidoarjo, 2023)
Breast milk (ASI) is the main nutrition recommended for newborns. The main obstacle in breastfeeding is the difficulty of breastfeeding because it is not smooth / milk production is disrupted so that exclusive breastfeeding is not achieved, by consuming foods that contain lactogogum is one of the efforts to increase milk production and the success of exclusive breastfeeding. one type of lactogogum that is currently being utilized because this type of plant is easy to plant and easy to get in the family yard is Moringa leaves. Objective: To determine the effect of moringa leaf powder on breast milk production in postpartum mothers in the Serpong 1 South Tangerang Health Center Area in 2023 Methodology: This type of research is quantitative with experimental design. This study used a quacy experimental design with two non-equivalent pretest-posttest groups. Sampling in this study using purposive sampling technique which amounted to 34 respondents. The analysis used is the Wilcoxon and Mann Whitney Test. Research Results: There is an effect of using moringa leaf powder on increasing breast milk production (p value 0.001) in postpartum mothers. Conclusion: Moringa leaf powder can increase breast milk production in postpartum mothers at Serpong 1 Health Center, South Tangerang in 2023. Suggestion: It is expected that moringa leaf powder can be consumed by postpartum mothers to prepare for the breastfeeding period so that they can provide exclusive breastfeeding.